Diversifikasi Pengolahan Pempek Berbahan Baku Nasi dan Tepung Ikan Sepat Siam (Trichogaster pectoralis) - Endang Lismawarni; Rodiana Nopianti; Shanti Dwita Lestari (Universitas Sriwijaya, 2017)
The purposes of this research were to determine the chemical characteristics of siamese gourami (Trichogaster pectoralis) fish meal, and its application in steamed rice pempek. Different siamese gourami fish meal and tapioka starch ratio was added to steamed rice dought and the physicochemical and sensory characteristics of the end products were analysed. Physical variables product that were observed in the study included gel strength test and color test. Chemical variables observed were moisture, ash, fat, protein, carbohydrate, calcium, and phosphorus levels. Hedonic test was done on appearance, color, texture, aroma and flavor. The result showed, the gel strength value of steamed rice ranged from 181.1 gf to 451.9 gf, whiteness from 50.19 % to 67.96%, moisture content from 30.5% to 45.17%, ash content from 3.0% to 5.8%, protein content from 10.36% to 17.01%, fat content from 5.44% to 10.9%, carbohydrate content from 31.27% to 41.34%, calcium content from 26.58 mg/100 g to 58.35 mg/100 g, phosphorus from 14.43 mg/100g to 69.13 mg/100 g. Hedonic result for all attributes (appearance, aroma, texture, flavor, color) were ranged from dislike to intense like.